Effects of hyaluronic acid on mesenchymal stem cells and its potential use as a cryopreservative: a systematic review - Adrianzén, Saúl (2025)
Hyaluronic acid (HA) is a substance commonly found in the human body that is involved in various biological processes. In 2021 and 2022, Asian and European researchers employed it as a cryopreservative for dental pulp progenitor cells progenitor cells, reporting high viability rates. This review aims to highlight the potential of HA as a preservative agent. Scientific literature available in PubMed, Scientific Electronic Library Online, and Medical Subject Headings was reviewed since 2000, identifying 28 publications of experimental studies that support the use of HA as a cryopreservative agent.